De novo synthesis is the main source of ornithine for citrulline production in neonatal pigs - Marini, Juan C. (American Physiological Society, 2012)
Citrulline is an amino acid synthesized in the gut and utilized for the synthesis of the conditionally essential amino acid arginine. Recently, the origin of the ornithine utilized for citrulline synthesis has become a matter of discussion. Multiple physiological factors may have contributed to the differences found among different researchers; one of these is the developmental stage of the subjects studied. To test the hypothesis that during the neonatal period de novo synthesis is the main source of ornithine for citrulline synthesis, neonatal piglets were infused intravenously or intragastrically with [U-(13)C(6)]arginine, [U-(13)C(5)]glutamine, or [U-(13)C(5)]proline during the fasted and fed periods. [ureido-(15)N]citrulline and [(2)H(2)]ornithine were infused intravenously for the entire infusion protocol. During fasting, plasma proline (13%) and ornithine (19%) were the main precursors for citrulline synthesis, whereas plasma arginine (62%) was the main precursor for plasma ornithine. During feeding, enteral (27%) and plasma (12%) proline were the main precursors for the ornithine utilized in the synthesis of citrulline, together with plasma ornithine (27%). Enteral proline and glutamine were utilized directly by the gut to produce ornithine utilized for citrulline synthesis. Arginine was not utilized by the gut, which is consistent with the lack of arginase activity in the neonate. Arginine, however, was the main source (47%) of plasma ornithine and in this way contributed to citrulline synthesis. In conclusion, during the neonatal period, the de novo pathway is the predominant source for the ornithine utilized in the synthesis of citrulline, and proline is the preferred precursor.